POSTOPERATIVE ARRHYTHMIAS AFTER CORONARY ARTERY BYPASS GRAFTING A COMPARISON BETWEEN ’˜OFF PUMP’ AND ’˜ON PUMP’ CABG - Iqbal, Javed; Ghaffar, Abdul; Shahbaz, Ahmad; Sami, Waqas; Khan, Jawad Sajid (Journal of Ayub Medical College Abbottabad, 2010)
Background: Coronary artery bypass without cardiopulmonary bypass (CPB) has gained popularity recently with the development of devices that allow for improved exposure and standardization in off pump coronary artery bypass surgery. Off pump coronary artery bypass surgery reduces some of the morbidities traditionally attributed to CPB. The primary goal of off pump coronary artery bypass surgery is to provide an equally comprehensive operational result as the conventional operation. The purpose of the study was to compare intra operative and postoperative arrhythmias in off pump coronary artery bypass (OPCAB) verses conventional CABG. Methods: This study was a sub-group as part of a randomised control trial and was conducted from January 2006 to March 2007 at Punjab Institute of Cardiology. One hundred patients were included in ’˜on pump’ group-A, and 100 patients in ’˜off pump’ group-B. Results: Thirty-three patients in group-A and 22 in group-B developed arrhythmias. Twenty-six patients developed atrial fibrillation in group-A and 16 patients in group-B. Mortality due to arrhythmias was 5, three were in on pump group, and 2 were in off pump group. Conclusion: There is non-significant tendency towards less frequency of postoperative arrhythmias in the off pump patients as compared to on pump coronary artery bypass surgery patients. Keyword: CABG, Coronary Artery Bypass Grafting, off pump, on pump, cardiopulmonary bypass